Strategi Komunikasi Politik “Nyantri” Prabowo Subianto dalam Memenangkan Pilpres 2024 - Hafid, Hafid; Jannah, Siti Raudhatul; Jauhari, Minan (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
Abstract The 2024 general election involved three candidates—a couple of presidential candidates and vice presidents. They're struggling to win the number one seat in the Republic. Each one of them uses the best political strategy to gain the people's sympathy. One of them is Prabowo Subianto, a presidential candidate who has